Canopy Research in Nepal Himalayas: Opportunities and Challenges - Devkota, Mohan P. (Journal of Institute of Science and Technology, 2019)
Despite a rapidly expanding interdisciplinary field worldwide, forest canopies of Nepal Himalayas are yet to be explored and the national conservation strategy still has to recognize the importance to identify it as an essential domain of canopy dwelling animals and plants. In the last few decades canopy science has emerged as a new discipline with more interdisciplinary and large-scale research possibilities are coming including canopy-atmosphere interactions, structural and functional aspects of canopy on biodiversity are a few among them. Canopies are important in supporting high terrestrial diversity and providing goods and services. Diverse rural mountain societies not only depend on goods and services provided by canopy but it also provides opportunities to explore sustainable use of resources for local livelihood generation. New frontiers of forest canopy research can also provide inputs to understand the potential impacts of climate change on the changing availability of goods and services affecting rural communities of Nepal. Yet, it still remains one of the unexplored and overlooked areas in the biodiversity sector of Nepal. Here, the opportunities of canopy research in Nepal Himalayas and various challenges associated with this are reviewed.